2023
DOI: 10.3389/fpubh.2023.1048210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic stress on smartphone addiction: A moderated mediation model

Abstract: IntroductionBased on the compensatory Internet use theory and diathesis-stress model, the present study explores the effects of chronic stress on smartphone addiction (SPA). As intolerance of uncertainty and emotion-related variables are important factors that affect addictive behavior, we explore the mediating role of intolerance of uncertainty and the moderating role of emotion differentiation.MethodsWe conducted a questionnaire survey of 286 participants (13.64% female; Mage = 22.88; SD = 3.77; range = 17–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This result confirms hypothesis 1. A recent study found that an intolerance of uncertainty mediates the link between chronic stress and SPA [ 13 ]. Another study [ 86 ] found that intolerance of uncertainty strongly predicts problematic smartphone use a month later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result confirms hypothesis 1. A recent study found that an intolerance of uncertainty mediates the link between chronic stress and SPA [ 13 ]. Another study [ 86 ] found that intolerance of uncertainty strongly predicts problematic smartphone use a month later.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, smartphone addiction (SPA), which develops from heavy smartphone use, has emerged as a complicated and growing public health concern, particularly among youth [ 9 , 10 ]. Addiction to smartphones is considered a behavioral addiction, implying that despite the considerable adverse effects of smartphone use, individuals continue to engage in excessive and uncontrolled smartphone usage [ [11] , [12] , [13] ]. SPA has been associated with psychological problems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This intervention could also be a treatment of choice based on our finding that symptoms of depression and anxiety were no longer significant after including IU in the model but also based on the existing knowledge that IU underpins various emotional and behavioral problems (Mahoney & McEvoy, 2012 ; McEvoy & Mahoney, 2012 ). Finally, Qiu and colleagues (Qiu et al, 2023 ) have also recently recognized that targeting IU in therapy could be a preventive measure for PSU/SA.…”
Section: Discussionmentioning
confidence: 99%